America, Jump-Started: World War II R&D and the Takeoff of the US Innovation System - Gross, Daniel P.; Sampat, Bhaven N. (American Economic Review, 2023)
During World War II, the US government’s Office of Scientific Research and Development (OSRD) supported one of the largest public investments in applied R&D in US history. Using data on all OSRD-funded invention, we show this shock had a formative impact on the US innovation system, catalyzing technology clusters across the country, with accompanying increases in high-tech entrepreneur-ship and employment. These effects persist until at least the 1970s and appear to be driven by agglomerative forces and endogenous growth. In addition to creating technology clusters, wartime R&D permanently changed the trajectory of overall US innovation in the direction of OSRD-funded technologies. (JEL H56, N42, N72, O31, O33, O38, R11)